2022
DOI: 10.3390/biom12030440
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal Lobar Degeneration Case with an N-Terminal TUBA4A Mutation Exhibits Reduced TUBA4A Levels in the Brain and TDP-43 Pathology

Abstract: Recently, disease-associated variants of the TUBA4A gene were identified in patients with amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here, we present the neuropathological report of a patient with the semantic variant of primary progressive aphasia with a family history of Parkinsonism, harboring a novel frameshift mutation c.187del (p.Arg64Glyfs*90) in TUBA4A. Immunohistochemistry showed abundant TAR DNA-binding protein 43 kDa (TDP-43) dystrophic neurite pathology in the frontal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…On the other hand, N-terminal TUBA4A mutations were identified in patients presenting with FTD, possibly with extrapyramidal symptoms (Perrone et al, 2017;Mol et al, 2021). We and others have shown that these mutations led to reduced TUBA4A levels in central nervous system tissues, suggesting a loss-of-function mechanism (Mol et al, 2021;Okada et al, 2021;Van Schoor et al, 2022). Interestingly, a downregulation of TUBA4A protein expression was also reported in the brain of sporadic ALS patients (Helferich et al, 2018), which we confirmed in this study via western blotting of motor cortex tissue.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, N-terminal TUBA4A mutations were identified in patients presenting with FTD, possibly with extrapyramidal symptoms (Perrone et al, 2017;Mol et al, 2021). We and others have shown that these mutations led to reduced TUBA4A levels in central nervous system tissues, suggesting a loss-of-function mechanism (Mol et al, 2021;Okada et al, 2021;Van Schoor et al, 2022). Interestingly, a downregulation of TUBA4A protein expression was also reported in the brain of sporadic ALS patients (Helferich et al, 2018), which we confirmed in this study via western blotting of motor cortex tissue.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, it was demonstrated that miR-1825 downregulation in ALS patient tissue led to increased tubulin-folding cofactor B (TBCB) levels, which led to the sequestration of TUBA4A and induced a decrease in its expression (Helferich et al, 2018). This gives an indication of the possible upstream events leading to decreased TUBA4A levels in ALS, aside from N-terminal TUBA4A mutations (Van Schoor et al, 2022). Importantly, we here demonstrate the causality of TUBA4A downregulation by showing that knockdown of the TUBA4A orthologue tuba8l2 in zebrafish embryos led to ALS-associated abnormalities, namely spinal axonopathy and behavioral deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it had been proven that mutation in certain genes could facilitate immune escape to promote tumor development. [35–37] Although extensive research has been conducted on the mutation of TUBA4A in various diseases, [38,39] our findings indicate that most genes, including TUBA4A, exhibit low mutation rates in PTC. Furthermore, the CNV of FAM107B and TUBA4A was not related to the OS in PTC.…”
Section: Discussionmentioning
confidence: 79%